2001
DOI: 10.1073/pnas.141199598
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior in living cells consistent with the tensegrity model

Abstract: Alternative models of cell mechanics depict the living cell as a simple mechanical continuum, porous filament gel, tensed cortical membrane, or tensegrity network that maintains a stabilizing prestress through incorporation of discrete structural elements that bear compression. Real-time microscopic analysis of cells containing GFP-labeled microtubules and associated mitochondria revealed that living cells behave like discrete structures composed of an interconnected network of actin microfilaments and microtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
543
3
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 638 publications
(595 citation statements)
references
References 43 publications
47
543
3
2
Order By: Relevance
“…Thus, the cytoskeleton not only stabilizes cell shape, and generates tension via an actinomyosin filament sliding mechanism: there is a measurable isometric tension that generates an internal "pre-stress". Thus, external mechanical loads are imposed on a pre-stressed structure (Wang et al, 2001). This can be compared, for instance, to the way our skeleton is held up against gravity through tensile linkages with surrounding muscle and tendon.…”
Section: Cellular Architecture and Tensegritymentioning
confidence: 99%
“…Thus, the cytoskeleton not only stabilizes cell shape, and generates tension via an actinomyosin filament sliding mechanism: there is a measurable isometric tension that generates an internal "pre-stress". Thus, external mechanical loads are imposed on a pre-stressed structure (Wang et al, 2001). This can be compared, for instance, to the way our skeleton is held up against gravity through tensile linkages with surrounding muscle and tendon.…”
Section: Cellular Architecture and Tensegritymentioning
confidence: 99%
“…4 Previous literature has suggested that microtubule polymerization occurs more freely in stretched cells, possibly because of the decreased compressional load placed on the microtubule. 10 Likewise, depolymerization is increased in cells that undergo compressive stresses, with a twofold decrease in polymerized tubulin seen in cells undergoing active compression.…”
Section: The Percent Of Apoptotic Cells (7sd) Is Shownmentioning
confidence: 99%
“…2 A whole field of mechanotransduction has emerged, and models such as tensegrity have been developed in an effort to describe how cells behave under various forms of stress, and how these stresses are translated into biochemical cascades and other cellular responses. [3][4][5] This is particularly true in the lung, a dynamic organ that undergoes continuously modulating exogenous forces due to cyclical respiratory patterns. In the injured lung, these forces can be even more prevalent, owing to mechanical ventilation or decreased airway space resulting from edema or compromised lung tissue.…”
Section: Introductionmentioning
confidence: 99%
“…However, proteolysis inhibition induced by either hypoosmolarity or insulin is sensitive to colchicine (45), indicating the involvement of microtubules. Indeed, microtubules significantly contribute to cellular mechanotransduction (46), but the colchicine sensitivity of proteolysis inhibition could also reflect a role of microtubules in autophagic vacuole formation and transport. Swelling-induced p38 MAPK activation is not affected by colchicine (47), which suggests an involvement of microtubules downstream of or apart from the p38 MAPK .…”
Section: Figmentioning
confidence: 99%